The genus Visiana Swinhoe (Lepidoptera: Geometridae: Larentiinae) in Australia: resurrection of two species from synonymy - Schmidt, Olga (Zootaxa, 2015)
Based on the study of morphological characters and DNA barcode (CO1) data, the present review revealed the existence of at least three species of Visiana Swinhoe (Lepidoptera: Geometridae: Larentiinae) in Australia. Visiana brujata (Guenée) is redescribed, and two species V. incertata (Walker), stat. rev. and V. repentinata (Walker), stat. rev. are resurrected from synonymy with V. brujata. Visiana breviaria (Walker), syn. rev., previously cited as a synonym of V. brujata, is now considered a synonym of V. incertata. Visiana brujata and V. incertata show close affinities with the sordidata group of species, whereas V. repentinata belongs to the vinosa species group. Images of adults and genitalia of all types are illustrated and the presence of the gnathos in the genus Visiana is discussed.